Writing and reading the scroll of Isaiah : studies of an interpretive tradition - Broyles, Craig C.; Evans, Craig A. (Vetus Testamentum, Supplements, 1997)
This first part of a 2-volume work, this study combines recent approaches that treat the formation and early interpretation of the final form of the book of Isaiah with the more conventional historical-critical methods that treat the use of traditions by Isaiah's authors and editors. Studies investigate Isaiah's use of early sacred tradition, the editing and contextualization of oracles within the Isaianic tradition itself, and the interpretation of the book of Isaiah in later traditions (as seen in the various versions of the text and various communities). Contributors of this volume include virtually all of the major scholars of Isaiah and the leading scholars of biblical interpretation in the intertestamental, New Testament, and early Jewish periods.